Frequency of Dental Caries and Status of Permanent Mandibular First Molar in Young Adults - Syed Ahmed Omer; Daud Mirza; Isra Ahmed; Omer Moosani; Syed Muzzamil Ali Shah (Journal of Bahria University Medical and Dental College)
Objectives: To determine (a) the frequency of dental caries (b) existing status including the presence of broken down roots(BDRs), missing and filled or unfilled status of permanent mandibular first molar in young adults. Materials and Methods: This study was conducted at out-patients clinics of Bahria University Medical and Dental College (BUMDC) from 1stJanuary 2014 to 30th November 2014. The total numbers of subjects were 1529. Out of which 928 were males(60.7%) and 601 were females (39.3%). The sample was collected through convenience sampling and the performa was designed which comprised of demographic data including age, gender, carious and filled/unfilled status of left and right permanent mandibular molar (36,46) and informed verbal consent was taken. Results: The study findings showed that higher caries incidence was present in left mandibular 1st molar (tooth # 36) as 232 individuals (15.17%) were affected by caries, compared to right mandibular 1st molar (tooth # 46) in which the affected individuals were only 209 (13.66%).Regarding the gender distribution, caries was present more in the males then the females as 179 males had caries and only 125 females were affected. Examined individuals have a better knowledge and awareness about oral hygiene practice as affected individuals were only 304 (19.9%). Least contribution was of filled teeth probably because of lack of availability of dental services, poor socioeconomic status and high treatment cost. Conclusion:Frequency of dental caries in left and right mandibular first molars in young adults was low with least contribution of filled teeth.